Topical Pimecrolimus 1% Cream in Treatment of Oral Lichen Planus - Taebunpakul, Patrayu; Chatchatee, Pantipa; Piboonratanakit, Pornpan; Thongprasom, Kobkan (Journal of Basic and Applied Pharmacology, 2015)
Oral lichen planus (OLP) is a common inflammatory disease of unknown etiology. The immunopathogenesis is T-cell mediated autoimmune disease. Various treatments have been tried to treat OLP but complete cure is difficult to achieve. Pimecrolimus is a new calcineurin inhibitor which can inhibit T-cell and mast-cell activation. We presented three cases of OLP patients treated with pimecrolimus 1 % cream 2 times daily for 4 weeks. All of the lesions showed improvement with nearly complete remission. No side effects were observed during 6-12 months follow-up in all cases.